Characterisation, emulation and by-emitter degradation analysis of high power semiconductor laser diodes - Amuzuvi, Christian Kwaku (2010)
The characterisation, emulation and by-emitter degradation analysis of two types of high power semiconductor laser diodes are presented in this thesis as part of an European Union (EU) project. An attempt is made using an accurate laser simulator called Speclase to learn more about the degradation of high power semiconductor laser diodes. Speclase being a single emitter simulation tool was transformed to model a bar i.e. multiple emitters, which we have named Barlase, through an external control interface written in Labview. The concept of Barlase was based on the fact that a bar is a monolithic block of multiple emitters connected in parallel with each other with a common voltage connected across them.